A primary reduced TCA flux governs substrate oxidation in T2D skeletal muscle - Gaster, Michael (Current diabetes reviews, 2012)
Our current knowledge on substrate oxidation in skeletal muscle in relation to insulin resistance and type 2 diabetes (T2D) originate mainly from in vivo studies. The oxidative capacity of skeletal muscle is highly influenced by physical activity, ageing, hormonal status, and fiber type composition, rendering it difficult to determine the contribution of heritable factors to the alteration in oxidative metabolism. Cultured human myotubes offer a unique model to distinguish between primary and environmental factors in the etiology of insulin resistance. The objective of this review is to summarise our studies on substrate oxidation in human myotubes established from lean, obese and T2D subjects, especially focusing on whether the increased respiratory quotient seen in T2D subjects is based on primary traits and whether changes in substrate oxidation may have a common explanation. Obtained results add further regulatory mechanism to our understanding of substrate oxidation in human skeletal muscle during normo- an pathophysiological conditions, focusing especially on the governing influence of a primary reduced TCA flux for the diabetic phenotype in skeletal muscle.